Research on Nonline-of-Sight Positioning Method of Intelligent Mobile Terminal Based on Intelligent Monitoring Architecture of Multimedia Sensor Network - Jianjun Liu (Advances in Multimedia)
With the continuous development of social economy, information resources have become more and more valued resources. Based on the intelligent monitoring architecture of the multimedia sensor network, this article proposes a nonline-of-sight positioning method that can fit the characteristics of autonomous movement for the object of intelligent terminal, that is, first draw the corresponding position trajectory according to the speed attribute of the node. On this basis, according to the relative position trajectory and radio frequency signal positioning, the two-by-two positioning of position and direction is comprehensively realized, and the positioning result is obtained; the positioning accuracy is evaluated according to the positioning of the radio frequency signal, and the false positioning result of the distorted radio frequency signal is stripped out to reduce the error influences. Practical results show that the method is effective and can meet the needs of positioning accuracy.